PENGARUH PENERAPAN STRATEGI PEMBELAJARAN CIRC (COOPERATIVE INTEGRATED READING AND COMPOSITION) TERHADAP KETERAMPILAN MEMBACA DAN MENULIS SISWA MADRASAH IBTIDAIYAH - Nurul Hidayah; Anwar Sa’dullah; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Cooperative Learning Strategy Type CIRC (Cooperative Integrated Reading and Composition) is a learning strategy that includes reading and writing activities, so it is suitable for use in language learning. This research is a quantitative research using experimental method with Posttest Only Control Design research design. posttest results show that the level of students' reading ability has increased by 10%, the level of students' writing skills has increased by 10%, and the value of students' knowledge has increased by 9%. And the results of the t test analysis obtained the results of t table < t count (1.99495 < 4.784). These results indicate that there is an effect of implementing the CIRC learning strategy on the reading and writing skills of grade 1 students.